Transforming Healthcare through AI: Enhancing Patient Outcomes and Bridging Accessibility Gaps (Journal of Artificial Intelligence & Research, 2024)
The integration of artificial intelligence (AI) in the healthcare sector is revolutionizing patient care and accessibility. AI-powered systems are transforming diagnostics, personalized treatment plans, and research methodologies, significantly improving patient outcomes and making healthcare more accessible to diverse populations. This paper explores the transformative potential of AI in healthcare, detailing the technological advancements, social benefits, and challenges associated with these innovations. Through an analysis of current technologies, case studies, and future prospects, we highlight how AI is bridging the accessibility gap and enhancing the quality of healthcare services.